Identifikasi Kendala Kualitas Ikan Asin Teri di UMKM Waluya Pulau Pasaran - Febrians, Indri Rizardi; Sundari, Susanti; Nudin, Burhan (Industrika : Jurnal Ilmiah Teknik Industri, 2025)
Waluya Small and Medium Enterprises (SMEs) manages a salted anchovy boiling operation located on Pasaran Island, Bandar Lampung, experiencing a significant decline in production output due to the high level of spoilage in the produced salted anchovies. This research aims to identify the constraints affecting the quality of the resulting Salted Anchovy through the approach of the Statistical Process Control (SPC) method, as well as providing corrective solutions. From the research results, factors were identified that affect the quality of salted anchovies produced by Waluya SMEs, namely: non-standard shape (31%); soft texture (28%); presence of foreign matter (23%); and incorrect sorting (18%). The problem of the non-standard shape of salted anchovies is caused by the careless salting and handling process. The solutions are to use containers that fit the size and type of anchovies and to implement staged salting. The problem of soft texture of salted anchovies is caused by uneven mixing of salt during the salting process. The solutions are to ensure sufficient salting time for the salt to penetrate evenly into the fish and to use appropriately sized containers. The problem of foreign matter in salted anchovies is caused by the traditional drying process. The solutions are to choose a clean drying location free from dust, dirt, and pests; and to use clean and easily cleaned bases. The problem of incorrect sorting of salted anchovies is caused by the manual process. The solutions are to train employee skills and invest in automatic sorting machines for the long term. Keywords: Identification, Quality, Salted Anchovies, SPC